2023
DOI: 10.1097/prs.0000000000010144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adding Carpal Tunnel Release or Trigger Finger Release to Carpometacarpal Arthroplasty on Postoperative Complications”

Abstract: Background: This study assessed whether adding trigger finger or carpal tunnel release at the time of thumb carpometacarpal (CMC) arthroplasty would increase postoperative opioid use, readmissions, complications, or development of complex regional pain syndrome (CRPS). Methods: Using the IBM MarketScan Research Databases from 2012 through 2016, the authors identified two CMC arthroplasty groups. The CMC-only group only had a CMC arthroplasty on the day of operation; the multiple-procedures group had a CMC ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…This challenge, combined with the ever-increasing competitiveness of successfully matching into surgical subspecialties, creates a barrier for students who attend schools that lack elective exposure opportunities. Previous studies have demonstrated that early exposure, lifestyle expectations, length of training, and role models significantly influence specialty choice [ [5] , [6] , [7] , [8] , [9] ]. Prior studies have also found that simulation and surgical skills trainers, as well as surgical electives during the preclinical years, may promote interest in the surgical field, further underscoring the value of specialty exposure upon residency selection [ 4 , 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This challenge, combined with the ever-increasing competitiveness of successfully matching into surgical subspecialties, creates a barrier for students who attend schools that lack elective exposure opportunities. Previous studies have demonstrated that early exposure, lifestyle expectations, length of training, and role models significantly influence specialty choice [ [5] , [6] , [7] , [8] , [9] ]. Prior studies have also found that simulation and surgical skills trainers, as well as surgical electives during the preclinical years, may promote interest in the surgical field, further underscoring the value of specialty exposure upon residency selection [ 4 , 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%